Ayahuasca-induced psychotic episodes: A systematic review from a case perspective. - Alcantarilla, Laura (2022)
Ayahuasca belongs to the group of plant-based or vegetal hallucinogens sharing their alterating effects on the state of consciousness and causing perceptual alterations. Traditionally used as a concoction in ceremonial rites aimed to achieve experiences of spiritual or curative content, its use has expanded throughout centuries, reaching our current cultural context, where it is used by small groups guided by purposes of personal growth. The experience usually lasts a few hours and the effects are usually self-limited. We describe the case of a patient who developed a manic episode with psychotic symptoms after experimental consumption of ayahuasca. In addition, a systematic review of published cases of sustained psychotic symptoms after the consumption of ayahuasca is carried out. There are few experimental studies of the relationship between ayahuasca and psychotic experiences, although a good safety profile has been determined in single administrations to healthy subjects. In the present study, the results suggest that the appearance of psychotic episodes associated with ayahuasca consumption is an infrequent phenomenon and seem to be related to vulnerability characteristics such as personal or family history of severe mental disorder or the concomitant use of other drugs, particularly cannabis.